Clinical and pathological characteristics of metabolic dysfunction-associated steatotic liver disease and the key role of epigenetic regulation: implications for molecular mechanism and treatment - Yijing Li; Lijie Li; Yishuo Zhang; Jing Lu; Xiaolei Tang; Chaoran Bi; Yanan Qu; Jingmei Chai (Therapeutic Advances in Endocrinology and Metabolism)
Nonalcoholic fatty liver disease (NAFLD), also called metabolic dysfunction-associated steatotic liver disease (MASLD) is a prevalent syndrome marked by liver fat accumulation in the absence of significant alcohol consumption, encompassing simple fatty liver, nonalcoholic steatohepatitis (NASH), and advanced stages such as fibrosis and cirrhosis. Its incidence has surged globally, impacting up to 40% of the population, with a doubling of cases in China over a decade. NASH, a severe form, can progress to liver cirrhosis and cancer, posing a substantial health burden, especially among individuals with type 2 diabetes. Projections indicate a steep rise in NASH cases, necessitating urgent interventions beyond lifestyle modifications, such as innovative pharmaceuticals. Early diagnosis is crucial, yet current tools have limitations, highlighting the need for noninvasive, scalable diagnostic approaches. Advances in imaging and biomarker identification offer hope for early detection. Epigenetic factors play a significant role in MASLD pathogenesis, regulating key molecular mechanisms. Addressing MASLD requires a multifaceted approach, integrating lifestyle interventions, pharmacotherapy, and emerging therapeutics, against the backdrop of an evolving landscape in disease management.